2010
DOI: 10.1002/mop.25719
|View full text |Cite
|
Sign up to set email alerts
|

A time‐domain measuring technique for ultra‐wide band antennas

Abstract: The measured IL of the miniature DBRs are 0.55 dB (parallel capacitors) and 0.44 dB (series capacitors), respectively. This leads to unloaded quality factors equal to 98 and 110, respectively. Hence, when the capacitors are connected in series a 12% improvement of unloaded quality factor of the miniature DBR can be obtained. The obtained %M are 76% (parallel) and 70% (series). The 6% difference is simply due to the meander realization used in the first case 0. CONCLUSIONSA new miniaturized DBR topology has bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…In a previous article , we showed that by averaging the transfer function of a set of two antennas in the intermediate‐field zone the result converges to the far‐field one. As a side benefit of averaging with the proposed method, one can therefore include in the distance range measuring points located in the intermediate‐field region.…”
Section: Effects Of Reflection and Diffraction On Gain Measurements mentioning
confidence: 95%
See 2 more Smart Citations
“…In a previous article , we showed that by averaging the transfer function of a set of two antennas in the intermediate‐field zone the result converges to the far‐field one. As a side benefit of averaging with the proposed method, one can therefore include in the distance range measuring points located in the intermediate‐field region.…”
Section: Effects Of Reflection and Diffraction On Gain Measurements mentioning
confidence: 95%
“…Based on a contribution that we have previously published [6], we also found that the distance-averaging technique makes it possible to reduce the distance between antennas below the lowest limit of the far-field region.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…Time‐domain reflectometry (TDR) is a well‐known technique that is typically used to localize impedance discontinuities along a line as a function of time (or distance) in electronic systems . A challenging problem in TDR is resolving closely‐spaced discontinuities.…”
Section: Introductionmentioning
confidence: 99%
“…It has recently been used successfully in the characterization of antennas in [5] and [6]. The motivation behind this is twofold: A TDR is less costly than a vector network analyzer (VNA) [5], but more importantly the time-localization of the energy in the test signal means that the user can dispense with the anechoic chamber that is required for antenna measurements with a sinewave exciting signal.…”
Section: Introductionmentioning
confidence: 99%